International students in the South African higher education system: A review of pressing challenges - Dominguez-Whitehead, Yasmine; Sing, Nevensha (Unisa, 2015)
The internationalisation of the South African higher education (HE) system, has involved (among other developments) the steady increase of international student enrolment, particularly from other African nations. While there has been a considerable increase in the percentage of international students over the past few decades, little is known about the challenges they confront and the ways in which socio-political and economic issues facing South Africa and the HE system may impact them. This article focuses on significant features of the South African HE system and considers some of the theoretical challenges faced by international students within this context. Pressing socio-political and economic issues facing South African HE specifically, and the nation more generally, are highlighted and in turn their relevance for challenges faced by international students relating to xenophobia, discrimination and financial difficulties are addressed.
Keywords: International students – South Africa; Xenophobia in tertiary education – South Africa; International students – Financial difficulties